Semantic Web Approach of Integrating Big Data- A Review - Ahmed, Jeelani; Ahmed, Muqeem (International Journal of Computer Sciences and Engineering, 2018)
Semantic Web is spread by World Wide Web Consortium (W3C) and international standardization body of the web. It is an extended form of the current web which provides an easier way to search, reuse, combine and share the information. Therefore Semantic Web is subsequently viewed as an integrator crosswise over various content, data applications, and frameworks. Today’s big data is usually pronounced as consisting of 3 V’s: volume, variety, and velocity. Variety of data discusses to deal with different formats of data and a large number of various data sources. Thus the problems of big data variety are important for solving many real-world difficulties. Semantic Web is used as an integrator to incorporate data from various kinds of sources like web services, relational databases, and spreadsheets etc. and in different formats. Due to the presence of data heterogeneity, this work presents various difficulties that may not be totally settled with the existing system. This paper is an attempt to focus on the various challenges that involved in integrating data from different types of sources and how different semantic web technologies and tools are used for the integration of disparate data.